PUBLIC’S BELIEFS ABOUT PSYCHOLOGICAL DISORDER, GONDAR, ETHIOPIA - Shebabaw, Mengesha Endalew; Gebeyehu, Kelemu Fenta; Sewasew, Daniel Tsehay (Innovare Journal of Social Sciences, 2014)
Abstract Objective: The main purpose of this study was to assess Beliefs hold by the publics about mental illness in the case of Gondar town. Methods: Data were collected from 371 participants on belief about psychological disorder from the public of some selected Kebeles of Gondar town. The participants were selected using multistage cluster sampling techniques. The data were analyzed using inferential statistics specifically t-test and one way ANOVA. Results: The study revealed that females have negative belief in psychological disorder than males while age and educational level of the participants does not influence belief about psychological disorder. In belief about psychological disorder there were three factors that include Dangerousness, Untrustworthiness and embarrassment and incurability factors. Conclusion: The research finding revealed that there exist statistically significant differences in beliefs about psychological disorder among the publics across sex and educational levels. Â Â Keywords: Belief about psychological disorder, dangerousness, Untrustworthiness and embarrassment factor and incurability factors.Â